Naïve Bayes classifier assisted automated detection of cerebral microbleeds in susceptibility-weighted imaging brain images - Ateeq, Tayyab; Faheem, Zaid Bin; Ghoneimy, Mohamed; Ali, Jehad; Li, Yang; Baz, Abdullah (Biochemistry and Cell Biology, 2023)
Cerebral microbleeds (CMBs) in the brain are the essential indicators of critical brain disorders such as dementia and ischemic stroke. Generally, CMBs are detected manually by experts, which is an exhaustive task with limited productivity. Since CMBs have complex morphological nature, manual detection is prone to errors. This paper presents a machine learning-based automated CMB detection technique in the brain susceptibility-weighted imaging (SWI) scans based on statistical feature extraction and classification. The proposed method consists of three steps: (1) removal of the skull and extraction of the brain; (2) thresholding for the extraction of initial candidates; and (3) extracting features and applying classification models such as random forest and naïve Bayes classifiers for the detection of true positive CMBs. The proposed technique is validated on a dataset consisting of 20 subjects. The dataset is divided into training data that consist of 14 subjects with 104 microbleeds and testing data that consist of 6 subjects with 63 microbleeds. We were able to achieve 85.7% sensitivity using the random forest classifier with 4.2 false positives per CMB, and the naïve Bayes classifier achieved 90.5% sensitivity with 5.5 false positives per CMB. The proposed technique outperformed many state-of-the-art methods proposed in previous studies.
Keywords: Automated detection; Brain bleed; Brain disorders; Brain images; Cerebral microbleeds; False positive; Hemosiderin deposit; Naive Bayes classifiers; Random forest classifier; Susceptibility weighted Imaging; Bayes Theorem; Brain; Cerebral Hemorrhage; Humans; Image Interpretation, Computer-Assisted; Magnetic Resonance Imaging; brain bleeds; cerebral microbleeds; hemosiderin deposits; naïve Bayes classifier; random forest classifier